Speed of movement of first instar larvae of Sagalassa valida (Lepidoptera: Glyphipterigidae) - SÁENZ-A., ADRIANA; OLIVARES, WILLIAM (Revista Colombiana de Entomología, 2008)
Sagalassa valida, the oil palm rootworm (Elaeis guineensis), is one of the most important pests from Western Colombia, Tumaco (Nariño). However, there is no knowledge about the biology of the larval stages. Therefore to manage this insect, a study was established on the speed of movement of the first instar larvae in greenhouse palms. To do this, Polyvinyl chloride (PVC) tubes were used with four holes of different diameters 0, 5, 10 and 15 cm, which were infested with S. valida eggs. Every 24 hours up to 96 hours the behavior and movement was determined according to the depth at which roots were found. At the end of the assay, it was concluded that larvae did not exceed a depth of 3 cm, finding the greatest percentage in the roots located practically on the surface of the soil. The larvae consume quaternary and tertiary roots starting from their apex, making circular and longitudinal movements. The time and depths showed significant effects on the abundance of larvae in the soil and palm roots.